INVESTIGATING CORRELATION BETWEEN READING STRATEGIES AND READING ACHIEVEMENT ACROSS LEARNING STYLES - Syaiful Islam (Universitas Islam Negeri Alauddin Makassar, 2019)
The study was aimed to analyze the interrelationship between metacognitive reading strategy and reading achievements, the correlation between cognitive reading strategy and reading achievement, and to know the effect between metacognitive and cognitive strategy used by learners across their learning styles. This study used correlation research. The number of populations was 315. The researcher chose 113 Senior High EFL students at MA Nurul Jadid. Questionnaire and reading comprehension test were used to collect data. The researcher used two questionnaires to measure reading strategies used by the students and students’ learning styles. SPSS V. 20 was used to analyze questionnaires’ data. Descriptive statistics was applied to calculate the mean and standard deviation of 40 individual reading strategies. The results were: metacognitive and cognitive strategies were used in high and medium level when students did the tests. Metacognitive strategy significantly correlated with reading achievement where correlation coefficient is greater than critical value of correlation coefficient while cognitive strategy does not relate mutually to reading achievements. Then, reading strategies significantly affected students’ reading achievement.